The impact of stratified management of Ki-67 on the prognosis of small-cell lung cancer - Xiaofang Zhang; Mingyang He; Guanghua Zheng; Junjun Bai (BMC Cancer)
Abstract Objective The Ki-67 protein is frequently employed in pathological immunohistochemistry to indicate cell proliferation activity. The principal aim of this study was to examine the impact of stratified management of Ki-67 on the clinicopathological characteristics and prognosis of patients with small-cell lung cancer (SCLC). Methods A total of 175 patients with SCLC who underwent surgical treatment were included in the study, with available data on the results of postoperative immunohistochemistry of the Ki-67 protein. A retrospective analysis was conducted to investigate the correlation between the protein and various clinicopathological features of SCLC, as well as its impact on survival. Results The cut-off value for the Ki-67 level was determined to be 75% through receiver operating characteristic (ROC) analysis. An elevated Ki-67 level was found to be associated with preoperative chemotherapy (χ2 = 4.980, P = 0.028), preoperative radiotherapy (χ2 = 4.600, P = 0.032), T stage (χ2 = 4.173, P = 0.041), TNM staging (χ2 = 10.472, P = 0.005), and lymph node involvement (χ2 = 16.721, P < 0.0001). The results of the survival analysis indicated that patients with SCLC exhibiting high levels of Ki-67 had a poorer prognosis than those with low Ki-67 levels (P = 0.0004). This was particularly evident in patients aged 60 years or older (P = 0.034), in males (P = 0.046), smoking for a minimum of 30 years (P < 0.001), advanced T staging (T3 + T4) (P = 0.031), lymph node involvement (P = 0.038), and TNM staging (P = 0.015), were associated with poorer outcomes. The univariate Cox regression analysis indicated that exposure to tobacco consumption (P = 0.040), pathologic T stage (P = 0.047), lymph node metastasis (P = 0.002), TNM staging [Stage I vs. II (P = 0.016), Stage I vs. III (P = 0.003)], and Ki-67 positive rate (P < 0.001) were the factors related to prognosis in SCLC. The results of the multivariate regression analysis indicated that T stage(HR: 1.519, 95% CI: 1.116–2.015, P = 0.022), TNM staging[Stage I vs. III (HR: 2.310, 95% CI: 1.320–4.040, P < 0.001)], and Ki-67 expression(HR: 1.405, 95% CI: 1.025–1.810, P < 0.001) was identified as an additional risk factor for SCLC-related mortality. Conclusion In summary, the Ki-67 protein is not only strongly associated with the malignant characteristics of SCLC, but also the stratification of Ki-67 has significant implications for the treatment and prognosis of patients with small-cell lung cancer. Clinical trial number Not applicable.